The family-support needs of Zimbabwean asylum-seeking families living with their disabled children in the Western Cape Province of South Africa - Tarusarira, Willson (Department of Health and Rehabilitation Sciences, 2016)
There is much evidence indicating that asylum - seeking families living with a child with disability experience poverty to a greater degree than those living without one. In the South African context, Zimbabwean asylum - seeking families that are driven into the country by poverty, lack of health facilities for their disabled children and discrimination are seriously disadvantaged by their lack of citizenship. This study on the family - support needs, perspectives and experiences of Zimbabwean asylum - seeking families living with children with disabilities explores the accumulation of impacts when these families attempt to access assistance, education and health care in South Africa. I begin with these families' background in Zimbabwe, a background on immigration into South Africa and a discussion of the effects of the country's immigration policy on immigrant families with disabled children. I then present a study carried out in Cape Town, South Africa, where 10 interviews were conducted with families of disabled children and 2 interviews with key informants from People Against Suffering, Oppression and Poverty (PASSOP), a local non - governmental organisation that deals with Cape Town - based refugees and asylum seekers from all over the world. The respondents were all Zimbabweans with children with disabilities. The findings indicate that Zimbabwean asylum families living with disabled children like any other asylum seeking families gain access to health care and education in Cape Town - South Africa. Though they are able to access health and education, the findings suggest that they face serious challenges, such as discrimination and stigmatisation. Zimbabwean asylum seeking families living with their disabled children are discriminated on the basis of their nationality, and they are more seriously disadvantaged by their lack of access to financial support, in the form of care - dependency grants, and by their limited access to disability support networks. The study concludes by recommending that the status of disabled immigrants and their families be revised with regard to the support that these families require and are able to access.